2016
DOI: 10.2147/jhc.s96085
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of localized hepatocellular carcinoma: patient selection and special consideration

Abstract: Localized hepatocellular carcinoma (HCC) refers to a solitary or few tumors located within either the left or right hemiliver without evidence of bilobar or extrahepatic spread. This term encompasses a heterogeneous morphology with no regard to stage of prognosis of the disease. Surgical resection remains the mainstay of curative treatment for the localized HCC. Various biochemical and radiological tests constitute an indispensible part of preoperative assessment. Emergence of laparoscopic hepatectomy has brou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 139 publications
0
13
0
Order By: Relevance
“…Liver resection remains the main curative option for HCC [29]. However, TACE is the most widely utilized and is considered the first-line treatment for patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Liver resection remains the main curative option for HCC [29]. However, TACE is the most widely utilized and is considered the first-line treatment for patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is regarded as the main curative therapy for HCC. [ 15 18 ] Previous studies have revealed that sustained HBV replication is strongly associated with HCC recurrence in CHB-related HCC patients after surgery. [ 19 ] Recent studies have confirmed that NAs can decrease the recurrence rate in CHB-related HCC patients receiving hepatic resection.…”
Section: Introductionmentioning
confidence: 99%
“…H epatocellular carcinoma (HCC) is responsible for over 90% of primary hepatic malignancies and considered the sixth most commonly diagnosed malignant disease in the world 1 . Due to its late diagnosis, the average patient survival ranges approximately from six to 20 months, with a fiveyear survival inferior than 12% 2 .…”
Section: Introductionmentioning
confidence: 99%